A Preliminary Experimental Study of Minority Stress, Startle Reactivity, and Alcohol Use among Heavy Drinking Sexual Minority Young Adults. (2nd January 2021) - Mereish, Ethan H.; Miranda, Robert
Abstract: Background: Sexual minorities (e.g. lesbian, gay, bisexual) are at increased risk for alcohol use disorder (AUD) compared to heterosexuals. The minority stress model postulates that disparities in AUD stem, in part, from stress specific to sexual minorities (e.g. heterosexism). However, little research has examined psychophysiological markers of minority stress reactivity and how psychophysiological stress reactivity is associated with lifetime minority stress and alcohol use among sexual minorities. Emotion modulation of the startle response is a well-established paradigm for capturing psychophysiological stress reactivity under controlled laboratory conditions. Purpose: This preliminary study is the first to use the startle experimental paradigm to examine psychophysiological reactivity to stigma among sexual minorities. Procedures: Sexual minority participants ( N = 20; 55% female), aged 18 to 27 years ( M = 21.80, SD = 2.65), were recruited from the community. We compared startle reactivity in response to three types of stimuli (stigma, negative, and neutral) among heavy drinking sexual minority young adults. Although statistically underpowered, we also explored the associations between startle reactivity and self-reported drinking behaviors and lifetime minority stress. Results: Both stigma and general unpleasant stimuli produced more psychophysiological stress reactivity than neutral stimuli among sexual minorities. Psychophysiological stress reactivity was correlated with greater quantity of drinks reported on drinking days in the past month, but not greater frequency. Additionally, lifetime exposure to minority stress was associated with a blunted reactivity to stigma stimuli. Conclusions: These findings provide methodological advances and important implications for minority stress theory and alcohol use among sexual minorities.